Distinct clinicopathological features of pulmonary primary angiomatoid fibrous histiocytoma: A report of four new cases and review of the literature. Issue 3 (12th December 2020) - Wang, Zheng; Zhang, Liping; Ren, Li; Liu, Dongge; Du, Jun; Zhang, Min; Lou, Ge; Song, Ying; Wang, Yin; Wu, Chunyan; Han, Guiping
Abstract : Background: The aim of this study was to highlight the clinicopathological features of pulmonary primary angiomatoid fibrous histiocytoma (PPAFH) to assist with a differential diagnosis. Methods: There were 10 previous reports in the literature and four new PPAFH cases reviewed in this study. Immunohistochemistry (IHC), fluorescence in situ hybridization (FISH) and DNA and RNA‐based next‐generation sequencing (NGS) was performed in the four new cases reported here. Results: In the four new PPAFH cases, the ages of occurrence were in patients age from 33 to 55 years and tumor sizes were from 1.5 to 8 cm. Three of four (75.0%) tumors were located in the endobronchus. The most common morphological changes included delineated fibrous capsule (100%, 4/4), lymphoplasmacytic cuff (100%, 4/4), and dense or richly lymphoplasmatic infiltration (100%, 4/4). IHC analysis revealed that the tumor cells of four cases expressed vimentin and TLE1, ALK and CD163 or CD68 was positive in three cases, epithelial membrane antigen (EMA), desmin was positive in two cases, and SMA focal positive expression was observed in two cases. EWSR1 gene rearrangement was positive in all PPAFH cases (100%, 4/4) by FISH detections and four cases were confirmed as EWSR1‐CREB1 fusion variant by DNA and RNA based NGS. No regional lymph nodes and distal metastasis, recurrences and death of disease after surgical excision were recorded in all four cases. Conclusions: PPAFH is a very unusual pulmonary primary mesenchymal tumor and the clinicopathological features are like other unusual sites counterparts, but with a smaller tumor size, related with large airway, with a tendency to exhibit benign biological behavior, with EWSR1 gene rearrangement and higher frequency of EWSR1‐CREB1 gene fusion. Key points: Significant findings in the study: In comparison with "classic somatic" and nonpulmonary visceral angiomatoid fibrous histiocytoma, pulmonary primary angiomatoid fibrous histiocytoma display distinct clinicopathological features and prognosis. What this study adds The study provided the pathological differential diagnostic criteria and clinico‐pathological features for pulmonary primary angiomatoid fibrous histiocytoma. Abstract : In comparison with "classic somatic" and nonpulmonary visceral angiomatoidfibrous histiocytoma, pulmonary primary angiomatoid fibrous histiocytoma display distinct clinicopathological features and prognosis.